Intelligent Gold Nanoparticles with Oncogenic MicroRNA‐Dependent Activities to Manipulate Tumorigenic Environments for Synergistic Tumor Therapy. Issue 15 (7th March 2022) - Wang, Xiangdong; Yang, Tianfeng; Yu, Zhi; Liu, Tao; Jin, Ronghua; Weng, Lin; Bai, Yongkang; Gooding, J. Justin; Zhang, Yanmin; Chen, Xin
Abstract: Tumorigenic environments, especially aberrantly overexpressed oncogenic microRNAs, play a critical role in various activities of tumor progression. However, developing strategies to effectively utilize and manipulate these oncogenic microRNAs for tumor therapy is still a challenge. To address this challenge, spherical nucleic acids (SNAs) consisting of gold nanoparticles in the core and antisense oligonucleotides as the shell are fabricated. Hybridized to the oligonucleotide shell is a DNA sequence to which doxorubicin is conjugated (DNA‐DOX). The oligonucleotides shell is designed to capture overexpressed miR‐21/miR‐155 and inhibit the expression of these oncogenic miRNAs in tumor cells after tumor accumulation to manipulate genetic environment for accurate gene therapy. This process further induces the aggregation of these SNAs, which not only generates photothermal agents to achieve on‐demand photothermal therapy in situ, but also enlarges the size of SNAs to enhance the retention time in the tumor for sustained therapy. The capture of the relevant miRNAs simultaneously triggers the intracellular release of the DNA‐DOX from the SNAs to deliver tumor‐specific chemotherapy. Both in vivo and in vitro results indicate that this combination strategy has excellent tumor inhibition properties with high survival rate of tumor‐bearing mice, and can thus be a promising candidate for effective tumor treatment. Abstract : Multiple functional spherical nucleic acids are developed to utilize and manipulate the tumorigenic genetic environment, and are able to perform tumor‐specific chain activities including oncogenic miRNAs (miR‐21 and miR‐155) inhibition, miR‐21‐dependent photothermal therapy, and miR‐155‐triggered chemotherapy for effective, accurate, and sustained tumor treatment.